2023
DOI: 10.3389/fphar.2023.1128219
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacist early active consultation (PEAC) on multidrug resistance organism treatment outcomes: A prospective historically controlled study

Abstract: Background and aim: Infectious disease (ID) consultation can improve multidrug-resistant organism (MDRO) treatment outcomes. However, the impact of clinical pharmacists’ ID consultation on MDRO therapy, especially early initiation, has not been reported. In this study, we try to explore the impact of the pharmacist early active consultation (PEAC) on MDRO patient management.Methods: We conducted a prospective historical controlled study based on PEAC in MDRO patients. The retrospective control group was patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Clinical pharmacist intervention can reduce the rate of unreasonable drug application [19,20,21], shorten the length of hospital stay of patients, lower the incidence of adverse drug reactions, and improve the effect of anti-infection treatment. Daijing Dong et al [22] found the rational rate of prophylactic use of antibiotics in class I incisions was signi cantly improved, and the course of medication was obviously reduced before and after the intervention of clinical pharmacists.Meanwhile, other studies also pointed out [23,24] that the participation of clinical pharmacists in the consultation and individualized adjustment of medication regimens can ensure that patients receive more economic and effective treatment, and have a positive impact on reducing the inhospital mortality of patients with multi-drug resistant infection. Our research further a rmed the value of clinical pharmacists in the rational use of antibiotics.…”
Section: Effect Of Re Ned Management Of Antibiotics Led By Clinical P...mentioning
confidence: 99%
“…Clinical pharmacist intervention can reduce the rate of unreasonable drug application [19,20,21], shorten the length of hospital stay of patients, lower the incidence of adverse drug reactions, and improve the effect of anti-infection treatment. Daijing Dong et al [22] found the rational rate of prophylactic use of antibiotics in class I incisions was signi cantly improved, and the course of medication was obviously reduced before and after the intervention of clinical pharmacists.Meanwhile, other studies also pointed out [23,24] that the participation of clinical pharmacists in the consultation and individualized adjustment of medication regimens can ensure that patients receive more economic and effective treatment, and have a positive impact on reducing the inhospital mortality of patients with multi-drug resistant infection. Our research further a rmed the value of clinical pharmacists in the rational use of antibiotics.…”
Section: Effect Of Re Ned Management Of Antibiotics Led By Clinical P...mentioning
confidence: 99%